2022
DOI: 10.3390/ijms23042235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Mechanisms of M. tuberculosis and SARS-CoV-2 Infections—Unexpected Similarities of Pathogenesis and What to Expect from Co-Infection

Abstract: Tuberculosis is still an important medical and social problem. In recent years, great strides have been made in the fight against M. tuberculosis, especially in the Russian Federation. However, the emergence of a new coronavirus infection (COVID-19) has led to the long-term isolation of the population on the one hand and to the relevance of using personal protective equipment on the other. Our knowledge regarding SARS-CoV-2-induced inflammation and tissue destruction is rapidly expanding, while our understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
(94 reference statements)
0
10
0
1
Order By: Relevance
“…The alterations in cell type profile during tuberculosis and COVID-19 are shown in Figure 2. Antigen-specific peripheral tissue effector Th1 cells can produce IFN-γ to activate a broad range of immunocompetent cells, including CD8+ T cells, ILC1, macrophages, and B-cells, which are involved in intracellular pathogen elimination [80,114].…”
Section: Discussionmentioning
confidence: 99%
“…The alterations in cell type profile during tuberculosis and COVID-19 are shown in Figure 2. Antigen-specific peripheral tissue effector Th1 cells can produce IFN-γ to activate a broad range of immunocompetent cells, including CD8+ T cells, ILC1, macrophages, and B-cells, which are involved in intracellular pathogen elimination [80,114].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic respiratory infections, such as TB, are more susceptible to hit by the COVID-19 disease. Active pulmonary tuberculosis can afford local reformations in lung immunity and influence host response to COVID-19(8) and also immune suppression related to this virus may cause certain difficulties in the diagnosis and management of TB( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Immune suppression caused by the SARS-CoV-2 virus may result in certain difficulties in the diagnosis and treatment of tuberculosis. Furthermore, long-term lymphopenia, hyperinflammation, lung tissue injury, and imbalance in CD4+ T cell subsets associated with COVID-19 could propagate M. tuberculosis infection and disease progression ( 10 ). The nasopharyngeal swab for RT-PCR SARS CoV-2 of the baby was negative, which likely indicated that no vertical transmission occurred ( 11 ).…”
Section: Discussionmentioning
confidence: 99%